1997
DOI: 10.2307/3284427
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cercariae from Stagnicola emarginata (Lymnaeidae) over 50 Years in Northern Michigan

Abstract: Stagnicola emarginata were collected from 3 northern Michigan lakes and examined for larval trematode infections. The structure of the trematode community was then compared with 2 previous studies conducted on Douglas Lake in order to determine what changes had taken place over a period of more than 50 yr and to examine the possibility of using trematodes as bioindicators of environmental quality. Species richness was reduced by half (from 16 to 8 species) from the first study conducted in 1936, along with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…They suggested that this resulted from a reduction in the number of vertebrates. Similar reasons, following human impacts on lakes, were proposed by Keas and Blankespoor (1997) to explain a decrease in digenean infections of S. emarginata in Michigan lakes over a period of 50 years. During this time, the prevalence declined from 61% to 13% and the species richness from 16 to 8 species.…”
Section: Discussionsupporting
confidence: 63%
“…They suggested that this resulted from a reduction in the number of vertebrates. Similar reasons, following human impacts on lakes, were proposed by Keas and Blankespoor (1997) to explain a decrease in digenean infections of S. emarginata in Michigan lakes over a period of 50 years. During this time, the prevalence declined from 61% to 13% and the species richness from 16 to 8 species.…”
Section: Discussionsupporting
confidence: 63%
“…This is not surprising as such studies are difficult; the natural hosts are often unknown, many species may have to be tested, and it is often difficult to obtain representatives of the expected natural hosts. Also, even if such experiments have been done, the morphological descriptions may lack precision or be compromised by the worms' developmental plasticity, and the local habitats and ecological conditions may have changed dramatically (Hsu and Hsu, 1957;Kinsella, 1971;Keas and Blankespoor, 1997). Thus, we end up with many tantalizing and often fuzzy dots that remain unconnected.…”
Section: Introductionmentioning
confidence: 99%
“…However, a complex survey of trematode communities in molluscs in Southeast Germany is missing, although the molluscs and their parasites are useful bioindicators of environmental changes in aquatic ecosystems over time (Keas and Blankespoor 1997). A high diversity of larval trematodes in biotopes indicates a good state of the environment because life cycles of trematodes can be successfully completed, particularly in undisturbed ecosystems.…”
Section: Introductionmentioning
confidence: 99%